Analisis Faktor yang Berperan dalam Kepribadian 'Social Entrepreneurship' - Dwiyadi Surya Wardana; Rahmat Alfikri (Jurnal Ilmiah Aset, 2018)
This research is based on the needs of the Indonesian nation on the development of equity. One of the parties that can help realize a great Indonesia is the entrepreneur, a new business entity that can be a bridge on the development gap. Knownby the name of social business and driven by social entrepreneurs. In this study there are 3 (three) independent variables that are innovation (X1), Proactiveness (X2), Risk Taking (X3) while the social entrepreneurship swah variable (Y). This study made the owners of social business or social institution that exist in Pontianak city area become respondent, from 100 respondents who become object in this research, with educational respondents aged 31-40 years, with highest education level of diploma equal. The majority of their social businesses have a workforce of 11-15 people, Innovation has no influence on the soul of social entrepreneurship, the ability to operate empirically has an influence on social entrepreneurship, empirical risk taking proven has a significant influence on social entrepreneurship. Together innovative personality, proactive and dare to take risks to the personality of social entrepreneurship, while the most proactive variable in social personality